Kesejarahan al-Qur’an dan Hermeneutika - Mudhofir Abdullah (JOURNAL OF QUR'AN AND HADITH STUDIES, 2014)
The Qur'an is not sufficient to be read in a single glass. Its significance continues to be present in a tumult of life. The Qur'an is also a book that concerns with human affairs and the environment. Because of its importance of the position, the Qur’an needs to be understood with intelligent and open perspectives. The more intelligent and open in reading the Qur'an, the meaning of the Qur’an will be more intelligent and open. Conversely, the more narrow and closedin reading the Qur'an, the meaning will be more narrow and closed. Therefore the readers of the Qur’an are encouraged to continue improving their capacity to understand the Qur'an very well. To master not only the basic sciences, but also other sciences related to the growth of human civilization. That is why a new method to read the Qur’an, such as hermeneutics and the historicity of the Qur’an, may, within certain limits, embrace the presence of al-Qur'an in life.